Deteksi Dini dan Peningkatan Pengetahuan Penyakit Osteoporosis pada Calon Jamaah Haji Di Yogyakarta : Indonesia - Marfianti, Erlina; Kasyiva, Mahdea; Sabila, Afila Biruni (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
Osteoporosis is a degenerative disease that can cause bone fractures. Early detection of osteoporosis reduces these complications. The Hajj is a pillar of Islam which in its implementation requires physical preparation and good health, including bone strength. Providing education on osteoporosis risk factors and early detection of osteoporosis can provide early action and prevent more severe conditions. The purpose of this community service is to provide education to prospective pilgrims regarding osteoporosis, and conduct osteoporosis screening for prospective pilgrims in Yogyakarta. This community service was carried out for 178 pilgrims candidate in Yogyakarta. This community service program consists of an osteoporosis early detection program with a bone mass density test, education on risk factors and osteoporosis management by creating infographics to distribute, as well as osteoporosis-related consultations. In community service the results of osteoporosis detection obtained data from 15 (8.43%) with normal bone density, 93 (52.25%) osteopenia, and osteoporosis there were 70 (39.33%). Provide education and consultation about osteoporosis, increase knowledge about risk factors and prevention of osteoporosis.